Clinical, Epidemiological, and Geospatial Characteristics of Patients Infected with Hepatitis C Virus Treated with Second-Generation Direct-Action Antivirals in a Reference Center in a Mesoregion of Sao Paulo State, Brazil - Pena, Danilo Zangirolami; Anadao, Murilo Fernandes; Flores, Edilson Ferreira [UNESP]; Okada, Mayara Namimatsu; Filho, Alexandre Martins Portelinha; Ferro, Rodrigo Sala; Prestes-Carneiro, Luiz Euribel (Mdpi, 2020)
Hepatitis virus infection is a major public health problem worldwide. Currently, Brazil has almost 700,000 cases. The Brazilian Unified Health System (SUS) provides therapeutic regimens for people infected with hepatitis C virus (HCV). We determined the clinical, laboratory, epidemiologic, and geospatial characteristics of patients infected with HCV treated with second-generation direct-action antivirals (DAAs) in a hospital reference center in Sao Paulo state, Brazil, using data from file records. A map was constructed using a geographic information system. From 2015 to 2018, 197 individuals received second-generation DAAs (mean age, 57.68 +/- 1.36 years; interquartile range, 56.22-59.14 years; 58.9% male; 41.1% female). Genotypes 1a and 1b accounted for 75.7% of cases and the prevalent therapeutic regimen was sofosbuvir/simeprevir. Sustained viral response accounted for 98.9% and the METAVIR score F3/F4 for 50.8%. Increased alanine transferase was significantly correlated with an increase in alpha-fetoproteins (p = 0.01), and severe necro-inflammatory activity (p = 0.001). Associated comorbidities were found in 71.6%, mainly coronary artery and gastrointestinal disorders. The cumulative incidence in the region was 2.6 per 10,000 inhabitants. Our data highlight the role of reference hospitals in Brazil's public health system in the treatment of HCV. Low incidence rates demonstrated the fragility of municipalities in the active search for patients.
Keywords: sustained virological response; comorbidities; gastrointestinal; depression; incidence